PENGARUH PEMBELAJARAN PPKN DALAM MEMBENTUK KARAKTER KEWARGANEGARAAN SISWA/I DI SMA NEGERI 1 CONCONG KABUPATEN INDRAGIRI HILIR - Novita Dewi; Jumili Arianto; Supentri Supentri (STKIP Pesisir Selatan, 2022)
This research is motivated by PPKn learning and the civic disposition of students at SMA Negeri 1 Concong, Indragiri Hilir Regency. The purpose of this study was to determine the effect of PPKn learning in Shaping the the civic disposition of Students at SMA Negeri 1 Concong, Indragiri Hilir Regency. The benefits of the results of this study for all parties are being a source of learning, contributing ideas in the world of education, especially those relating to the influence of PPKn learning in Shaping the the civic disposition of students in schools. This research method is descriptive quantitative, the data collection instruments used in this research are observation, interviews, documentation and questionnaires consisting of 16 statements. The population in this study were all students of SMA Negeri 1 Concong, Indragiri Hilir Regency, totaling 200 students. Sampling in this study used proportional random sampling technique. Then a simple random sampling technique was used with a sample of 50 students. Based on the results of research on the effect of PPKn learning in Shaping the the civic disposition of Students at SMA Negeri 1 Concong, Indragiri Hilir Regency, it can be concluded that there is a significant influence between PPKn learning in Shaping the the civic disposition of Students at SMA Negeri 1 Concong, Indragiri Hilir Regency of 74%